PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS DISCOVERY LEARNING PADA MATERI LINGKARAN KELAS VIII SMP - Kiki Guswira (Departemen Matematika, 2021)
This research has purpose to produce a valid and practical interactive learning multimedia based on discovery learning in the circle material of class VIII Junior High School. This research is a development research using the Plomp development model. The development procedure consists of three stages which include: (a) preliminary research phase, (b) development phase or prototyping phase and (c) assessment phase. At the preliminary research stage requires needs analysis, student analysis, curriculum analysis, and concept analysis. At the prototyping phase the product was designed using the Macromedia Flash Professional 8 application based on the discovery learning model. Furthermore, the product will be evaluated to obtain valid criteria through self-evaluation and expert reviews. After the product was declared valid, a one-to-one evaluation was conducted to obtain suggestions from students. In the assessment phase, a small group evaluation was carried out to obtain practicality. The results showed that the interactive learning multimedia based on discovery learning in the circle material of class VIII SMP was valid and practical. Keywords—Interactive learning multimedia, discovery learning, Plomp.